CONTEXTUAL THEMATIC INTERPRETATION OF CHILD MARRIAGE IN THE QUR’AN: RECONSTRUCTING MATURITY AND SOCIAL ETHICS IN INDONESIA - Thoat Stiawan; Nurcahaya Nurcahaya; Mualimin Mochammad Sahid; Mohammad Ikhwanuddin; Erna Dewi (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2025)
Child marriage remains a persistent social problem in Indonesia, despite significant legal reforms, notably the enactment of Law No. 16 of 2019 which raised the minimum legal age of marriage to nineteen years. However, empirical realities indicate that the practice continues to be widespread, largely reinforced by literalist religious interpretations that neglect the ethical spirit and broader objectives of Islamic jurisprudence. In response to this challenge, this study aims to critically re-examine Qur’anic verses that are frequently invoked to justify the marriage of minors through a contextual thematic interpretation (tafsīr mawd}ū’ī). This research employs a qualitative methodological framework by systematically identifying and thematically categorizing Qur’anic verses related to marriage, maturity (bulūgh), and intellectual discernment (rusyd), and parental responsibility. These verses are analyzed within their socio-historical context of revelation (asbāb al-nuzūl), followed by a contextual reinterpretation that engages contemporary legal norms and social realities in Indonesia. The findings demonstrate that although the Qur’an does not stipulate a specific chronological age for marriage, it consistently emphasizes comprehensive maturity, including physical, psychological, emotional, and financial readiness as a fundamental prerequisite. Furthermore, child marriage in the Indonesian context is shown to produce significant harm, particularly in relation to educational attainment, reproductive health, and long-term socio-economic justice. Such consequences contradict the ethical objectives of Islamic law (Maqās}id al-Sharī’ah), especially the protection of life, intellect, lineage, and human dignity. Accordingly, this study argues that a contextual thematic interpretation of the Qur’an provides a robust ethical and normative foundation to challenge literalist readings that legitimize child marriage. It further contributes to strengthening religiously grounded support for child protection policies and fostering a more humanistic and socially responsive Islamic discourse in contemporary Indonesia.